Efficacy and safety of teriflunomide in Asian patients with relapsing forms of multiple sclerosis: A subgroup analysis of the phase 3 TOWER study. (January 2019) - Miller, Aaron E.; Xu, Xianhao; Macdonell, Richard; Vucic, Steve; Truffinet, Philippe; Benamor, Myriam; Thangavelu, Karthinathan; Freedman, Mark S.
Highlights: Efficacy and safety of teriflunomide in Asian patients with relapsing MS were comparable to the overall TOWER population. No new or unexpected safety findings were observed. This analysis provides evidence of the clinical benefits of teriflunomide in a diverse patient population with relapsing MS. Abstract: In the phase 3 TOWER (NCT00751881) study, teriflunomide 14 mg significantly reduced annualized relapse rate (ARR) and risk of 12-week confirmed disability worsening (12-w CDW) vs placebo in patients with relapsing forms of MS (RMS). The TOWER population included an appreciable proportion of Asian patients. Reductions in ARR and 12-w CDW associated with teriflunomide 14 mg were comparable between the Asian and overall populations, as were the rates for adverse events and serious adverse events, with no new or unexpected safety findings. These observations provide further evidence to support the clinical benefits and safety profile of teriflunomide in a broad range of patients with RMS.